Signaling pathways and endogenous stem cell proliferation in Tribolium castaneum - Tank, William (My University, 2026)
Endogenous stem cells are responsible for tissue maintenance, remodeling, and repair in many organisms. This project explored whether signaling pathways associated with proliferation and apoptosis could be manipulated to alter endogenous stem cell activity during post-embryonic development, with long-term interest in how these mechanisms could eventually contribute to regenerative approaches. Initial pathway comparisons examined Wnt, Notch, TGF-β, and Hippo signaling. The Hippo pathway was selected for further investigation because of its direct involvement in regulation of proliferation, apoptosis, and tissue growth. Tribolium castaneum was chosen as the experimental model because its midgut contains accessible intestinal stem cell clusters (nidi) and supports strong systemic RNA interference (RNAi). Double-stranded RNA targeting Hippo pathway components including hippo (hpo), warts (wts), yorkie (yki), and salvador (sav) was injected into larval, pupal, and adult stages. Midgut tissues were evaluated using EdU incorporation assays, fluorescence microscopy, histology, RTqPCR, and RNASeq. Among the genes tested, salvador knockdown produced the strongest and most consistent phenotype. Midgut tissues displayed disrupted epithelial organization, widespread EdU incorporation, nuclear crowding, tissue fragility, and abnormal nidi morphology across developmental stages. Similar abnormalities were reproduced using an independent salvador dsRNA construct. RT-qPCR confirmed reduction of salvador transcript expression following RNAi treatment. RNASeq analysis following salvador knockdown identified transcriptional changes associated with epithelial organization, ion transport, stress responses, and cytoskeletal regulation rather than a clear enrichment of canonical proliferative signatures. The observed phenotype was therefore interpreted as dysregulated proliferative activity associated with loss of epithelial organization rather than controlled regenerative expansion. This work supports the use of Tribolium castaneum as a model for studying Hippo pathway function during post-embryonic intestinal remodeling and demonstrates that disruption of salvador produces extensive abnormalities in proliferative regulation and midgut organization.
Keywords: Stem cells, RNAi, RNASeq, RT-qPCR, Hippo pathway